IMPLEMENTASI KURIKULUM 2013 MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 WONOGIRI DAN SMP NEGERI 1 SURAKARTA TAHUN 2019 - Rojif Mualim; Ari Anshori; Mohamad Ali (Profetika: Jurnal Studi Islam, 2019)
Abstract: A curriculum is a container to determine the direction of education. Success and failure of education, are highly depended on the curriculum. The curriculum is the spearhead for the implementation of education. The curriculum is a container to determine the direction of education. Success and failure of education, are highly depended on the curriculum. The curriculum is the spearhead for the implementation of educational activities. The  curriculum 2013 divides attitude competencies into two, namely spiritual attitudes and social attitudes. The purpose of this study is to describe the natural findings regarding the implementation of the curriculum 2013 toward PAI subjects at SMP Negeri 1 Wonogiri and SMP Negeri 1 Surakarta, as well as the constraints and their carrying capacity. This study used qualitative research methods or field type research (field research), which is a research procedure that produces descriptive data sourced from written or oral words from people and observable behavior directed at the background and individuals as a whole. The subjects of this study were students and teachers of Islamic Religious Education, data collection techniques used observation, interviews and documentation. The results of this study indicated that the process of implementing the Curriculum 2013 in SMP Negeri 1 Wonogiri and SMP Negeri 1 Surakarta has been implemented by applying patterns or types determined by the government. However, from the implementation process there are obstacles, including: the distribution of the teacher and student handbooks, both textbooks from subject teacher deliberations (MGMP) and directly from the government, the assessment system were very complicated so that some teachers did not understand the assessment of the Curriculum 2013, some students did not have complete facilities such as laptops. In carrying capacity, students were always given direction on the tasks they have to complete, teachers were enthusiastic in implementing the Curriculum 2013, school programs namely school missions, determining the value of students was not only obtained from test scores but also from values of politeness, religion, practices, attitudes and others, the other teachers’s support excepting PAI subject, complete school facilities such as a comfortable class, LCD, white board, etc. Abstrak: Kurikulum merupakan sebuah wadah yang akan menentukan arah pendidikan. Berhasil dan tidaknya pendidikan, sangat bergantung dengan kurikulum. Kurikulum adalah ujung tombak bagi terlaksanya kegiatan pendidikan. Kurikulum 2013 membagi kompetensi sikap menjadi dua, yaitu sikap spiritual dan sikap sosial. Tujuan penelitian ini adalah untuk mendiskripsikan temuan-temuan alamiah perihal implementasi kurikulum 2013 pada mata pelajaran PAI di SMP Negeri 1 Wonogiri dan di SMP Negeri 1 Surakarta, serta kendala dan daya dukungnya. Penelitian ini menggunakan metode penelitian kualitatif atau berjenis field reseach (penelitian lapangan) yaitu prosedur penelitian yang menghasilkan data deskriptif yang bersumber dari kata-kata tertulis atau lisan dari orang-orang dan perilaku yang dapat diamati yang diarahkan pada latar dan individu secara utuh. Adapun yang menjadi subjek penelitian ini adalah siswa dan guru Pendidikan Agama Islam, teknik pengumpulan data menggunakan cara observasi, wawancara dan dokumentasi. Hasil penelitian ini menunjukkan bahwa proses implementasi Kurikulum 2013 di SMP Negeri 1 Wonogiri dan SMP Negeri 1 Surakarta sudah dilaksanakan dengan menerapkan pola atau tipe yang ditentukan oleh pemerintah, Akan tetapi dari proses implementasi itu ada kendalanya, antara lain: belum terdistribusinya buku pegangan guru dan siswa dengan baik, baik buku paket dari musyawarah guru mata pelajaran (MGMP) maupun langsung dari pemerintah, sistem penilaian sangat rumit sehingga tidak semua guru mengerti dan faham penilaian pada kurikulum 2013, tidak semua siswa memiliki fasilitas yang lengkap seperti laptop. Daya dukung, peserta didik selalu diberi pengarahan terhadap tugas-tugas yang harus mereka selesaikan, guru semangat dalam mengimplementasikan kurikulum 2013, program sekolah yaitu misi sekolah, penentuan nilai bagi siswa bukan hanya didapat dari nilai ujian saja tetapi juga didapat dari nilai kesopanan, religi, praktik, sikap dan lain-lain, Dukungan dari semua guru selain guru mapel PAI. Fasilitas Sekolah yang lengkap seperti misalnya kelas yang nyaman, LCD, White Board, dll.